2019
DOI: 10.1136/bmj.l5221
|View full text |Cite
|
Sign up to set email alerts
|

Design characteristics, risk of bias, and reporting of randomised controlled trials supporting approvals of cancer drugs by European Medicines Agency, 2014-16: cross sectional analysis

Abstract: ObjectiveTo examine the design characteristics, risk of bias, and reporting adequacy of pivotal randomised controlled trials of cancer drugs approved by the European Medicines Agency (EMA).DesignCross sectional analysis.SettingEuropean regulatory documents, clinical trial registry records, protocols, journal publications, and supplementary appendices.Eligibility criteriaPivotal randomised controlled trials of new cancer drugs approved by the EMA between 2014 and 2016.Main outcome measuresStudy design character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
102
2
4

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 134 publications
(109 citation statements)
references
References 96 publications
(127 reference statements)
1
102
2
4
Order By: Relevance
“…An extensive analysis of the FDA's oncological medicine approvals between 2006 and 2015 affirmed these observations (Rodríguez et al, 2019). Furthermore, clinical trials providing the evidence needed to underpin the regulatory approval process (hereinafter referred to as "registrational trials") can be prone to bias, which often remains inadequately reported (Naci et al, 2019). Moreover, the accelerated and conditional marketing authorization mechanisms launched by FDA and EMA respectively have further solidified the use of surrogate endpoints in clinical trials (Fleming, 2005;Downing et al, 2014;Hoekman et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…An extensive analysis of the FDA's oncological medicine approvals between 2006 and 2015 affirmed these observations (Rodríguez et al, 2019). Furthermore, clinical trials providing the evidence needed to underpin the regulatory approval process (hereinafter referred to as "registrational trials") can be prone to bias, which often remains inadequately reported (Naci et al, 2019). Moreover, the accelerated and conditional marketing authorization mechanisms launched by FDA and EMA respectively have further solidified the use of surrogate endpoints in clinical trials (Fleming, 2005;Downing et al, 2014;Hoekman et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Uncertain patient-relevant benefits of new drugs Several recent reports have found that newly authorised medicines often have questionable or no added patient-relevant benefits compared to already available, older treatments. [1][2][3][4][5][6] In a cohort of 216 drugs approved by the German drug regulatory authority between 2011 and 2016, the independent Institute for Quality and Efficiency in Health Care (IQWiG) judged that 22 (10 %) new drugs had substantial benefits compared to already available treatments, while 125 (58 %) drugs had no proof of added benefits. 1 Cohort studies of oncology drugs approved by the European Medicines Agency (EMA) 4 and the US Food and Drug Administration (FDA) 5 found that most drugs were approved without evidence of benefits on overall mortality or quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, an analysis of oncology drugs approved by the EMA between 2014 and 2016 reported that many pivotal trials underpinning drug approvals were of high risk of bias due to problems with the trial design and or trial conduct. 6 It has been argued that the threshold for new drug approvals has been lowered to accommodate the pharmaceutical industry's interests, 7 and researchers have advocated for more pragmatic, patient-relevant trials. 8 Field specific issues in psychiatry Systematic reviews, particularly of antidepressants for depression 9, 10 and of central stimulants for attention deficit hyperactivity disorder, [11][12][13] have highlighted problems of low generalizability of psychiatric drug trials, similar to those identified in pivotal oncology drug trials.…”
Section: Introductionmentioning
confidence: 99%
“…Ledford (2019), for example, argues that ethnicity is a major concern for geneticists with regard to studying cancer across populations, but is often overlooked in Western clinical trials for cancer. A recent study on cancer drugs approved by the European Medicines Agency (EMA) argued that almost all studies between 2014 and 2016 were at risk of bias (Naci et al 2019). Others have suggested that trials conducted by the pharmaceutical industry, as opposed to academic investigators alone, differ vastly with regard to their goals, whereby studies conducted by the pharmaceutical industry may not have the best interests of the patient as a concern, but rather focus on drug approval (Piccart et al 2007).…”
mentioning
confidence: 99%